State of Knowledge: Hydropower Environmental Mitigation Measures on the Lancang River - Geheb, Kim; Yu, Xuezhong (2017)
Chinese HPPs on the Lancang River have been developed for electricity generation, flood control, water supply, and navigation improvement. Hydropower was expected to play an increasingly important role in developing a low carbon economy and increasing resilience to climate change in China.